If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 1 + -1x + y Solving 0 = 1 + -1x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 0 + x = 1 + -1x + x + y Remove the zero: x = 1 + -1x + x + y Combine like terms: -1x + x = 0 x = 1 + 0 + y x = 1 + y Simplifying x = 1 + y
| 12x+3x-7=4x+31 | | 3x+3*(-3)=3 | | 5x+8+x=170 | | h=3(0)+1 | | 3x+3*3=3 | | -16h^2-49h-3=0 | | h=3(-2)+1 | | 3*(-2)+3y=3 | | h=3(-1)+1 | | .3(3z+7)+18.9=.5(3z-6) | | 5km+3=77km | | y-4=-x-1 | | 8-18=38 | | 8-4x=4-(2x+6) | | 9(2z+4)=-23 | | 3(6x+8)=11x-5 | | -4-3x(-2)= | | ept=qt | | -2(m+7)=-31 | | c=17cm | | 15+5x+6X=180 | | -y=5-4x | | 3x^2/2 | | -1=-3x+22x | | 4r+2r=-34 | | 6x-9=-4x+3 | | 8x+7-9=90 | | X=2/6=-19/6 | | 2x-1+4=-8 | | 2(m-8)=24 | | x+6=15.2 | | -3y+4x=27 |